2000
DOI: 10.1021/ma001205v
|View full text |Cite
|
Sign up to set email alerts
|

Living Radical Polymerization in Miniemulsion Using Reversible Addition−Fragmentation Chain Transfer

Abstract: Living radical polymerizations using reversible addition−fragmentation chain transfer (RAFT) have been conducted successfully in miniemulsions stabilized by nonionic surfactants. The miniemulsion stability was found to be a key issue. Both anionic and cationic surfactants were not able to maintain the original droplet morphology during the reaction. The application of nonionic surfactants allowed the controlled polymerization of methacrylate and styrene monomers, resulting in stable dispersions free of coagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
214
2
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(224 citation statements)
references
References 35 publications
5
214
2
3
Order By: Relevance
“…These include certain trithiocarbonates, xanthates, dithiocarbamates, and other compounds. The effectiveness of the RAFT agent depends on the monomer being polymerized and depends strongly on the properties of the free-radical leaving group R and the group Z which can be chosen to activate [44] (MMA), [44] AA [63] -7 [44] S, [14,44] (MMA) [6,44] -NC 8 [9,44] S, [9,14,44,46] AA, [6] MA, [44,64] NIPAM-XMA, [69] S-MAH, [70] MMA, [6,14,44,52] XMA, [65][66][67] EHMA-b-S, [68] EHMA-b-MMA-MA [68] VBz, [13,14] MMA, [68] BMA, [68] EHMA [68] …”
Section: Choice Of Raft Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include certain trithiocarbonates, xanthates, dithiocarbamates, and other compounds. The effectiveness of the RAFT agent depends on the monomer being polymerized and depends strongly on the properties of the free-radical leaving group R and the group Z which can be chosen to activate [44] (MMA), [44] AA [63] -7 [44] S, [14,44] (MMA) [6,44] -NC 8 [9,44] S, [9,14,44,46] AA, [6] MA, [44,64] NIPAM-XMA, [69] S-MAH, [70] MMA, [6,14,44,52] XMA, [65][66][67] EHMA-b-S, [68] EHMA-b-MMA-MA [68] VBz, [13,14] MMA, [68] BMA, [68] EHMA [68] …”
Section: Choice Of Raft Agentsmentioning
confidence: 99%
“…[9,68,82,102,[185][186][187][188][189][190][191][192][193][194][195] We showed that RAFT in miniemulsion can be used to produce polystyrene of narrow polydispersity in a batch process. [9] Some retardation is observed with dithiobenzoate RAFT agents.…”
Section: Raft In Heterogeneous Mediamentioning
confidence: 99%
“…Exemplificação da formação de blocos de copolímero via extensão de cadeia utilizando a técnica de polimerização RAFT [16] . a ser implementada em diversos sistemas homogêneos e heterogêneos de polimerização [7][8][9][10] , o que incluiu as emulsões, suspensões e dispersões [13] , além das primeiras comunicações relacionadas à polimerização RAFT em miniemulsão [34,35] . As emulsões poliméricas constituem de longe os sistemas dispersos mais bem estudados na área de polímeros.…”
Section: Polimerização Raft Em Miniemulsãounclassified
“…A Tabela 1 apresenta os estudos publicados até a presente data sobre a produção de polímeros que utilizaram a técnica RAFT em miniemulsão. Conforme revisado, a técnica de polimerização RAFT em miniemulsão já foi adaptada para os principais tipos de monômeros comerciais (como, por exemplo, estireno [28,34,35, , metacrilato de metila [35,54,68,[74][75][76][77][78][79][80] ), sistemas inversos [23,52,[81][82][83][84][85][86] e sistemas contínuos de polimerização [87][88][89] ). Além dos trabalhos citados na P(AM-co-AA) Inverso [83] P(NIPAM-b-PEO) Inverso [82] a Poliestireno (PSt), poli(metacrilato de metila) (PMMA), poli(buitl metacrilato (PnBMA), poli(hidroxietil metacrilato) (PEHMA), poli(butil acrilato) (PnBA), poli(acetato de vinila) (PVAc), Poliacrilamida (PAM), poli(ácido acrílico), poli(2-dimetilamino (metacrilato de etila)) (PDMAEMA), ácido metacrílico (MAA), acrilato de dodecafluoro heptil (DFHA), acrilamida (AM), ácido acrílico (AA), isopopil acrilamida (NIPAM), poli(óxido de etileno) (PEO).…”
Section: Polimerização Raft Em Miniemulsãounclassified
See 1 more Smart Citation